PENDIDIKAN KARAKTER SISWA DALAM IMPLEMENTASI PEMBELAJARAN TEMATIK KURIKULUM 2013 DI SEKOLAH DASAR - Sholihah, Mar Atun (CV. Amerta Media, 2020)
Character education is the right way to improve morale, character and character of children. Character education is a set of conscious efforts to instill good values or attitudes for students so that they can be realized in the environment and daily behavior. The current curriculum is the 2013 curriculum, where learning is thematic which no longer uses subjects, but uses themes as learning material. Character education by instilling character values in thematic learning should be carried out in all stages of thematic learning. So that when the teacher makes the lesson plan, he also analyzes the appropriateness of the appropriate character values that will be developed.Key Words: Character education, 2013 Curriculum, Thematic Learning